2020
DOI: 10.12928/telkomnika.v18i2.14785
|View full text |Cite
|
Sign up to set email alerts
|

Comparing random forest and support vector machines for breast cancer classification

Abstract: There are more than 100 types of cancer around the world with different symptoms and difficulty in predicting its appearance in a person due to its random and sudden attack method. However, the appearance of cancer is generally marked by the growth of some abnormal cell. Someone might be diagnosed early and quickly treated, but the cancerous cell most times hides in the body of its victim and reappear, only to kill its sufferer. One of the most common cancers is breast cancer. According to Ministry of Health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…Notwithstanding variations in the experimental outcomes, the SVM is equated to more traditional models in many of these studies. In contrast, other studies [13], [14], [16], [19] reported that the SVM grippingly outperformed several conventional models.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Notwithstanding variations in the experimental outcomes, the SVM is equated to more traditional models in many of these studies. In contrast, other studies [13], [14], [16], [19] reported that the SVM grippingly outperformed several conventional models.…”
Section: Introductionmentioning
confidence: 76%
“…The SVM employs the risk minimisation theory to establish the best separation hyperplane in multi-dimensional space to classify a bipartite outcome [11]. Initially, the SVM was designed for binary classification [12]; however, of late, the SVM is applicable for both classification and The performance of the SVM has been compared with other ML algorithms, such as Bayesian logistic regression, and decision tree [13], [14], random forest [15], [16], neural network [17], [18] and k-nearest neighbours [19], [20]. Notwithstanding variations in the experimental outcomes, the SVM is equated to more traditional models in many of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…We can use any classifier since it is a two-class problem; we used SVM with different kernels. The design of SVM is based on a large margin theory and gives very good results in many binary classification problems [ 43 , 44 , 45 , 46 ]. The SVM model is trained using the predictions of the training and the validation datasets.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Breast cancer is a condition in which cells grow out of control, resulting in a tumour that can spread throughout the body. Although the specific causes of breast cancer are unknown, researchers believe that aberrant cell growth is caused by a combination of genes, lifestyle, environment, and hormones [2]. This breast cancer must be detected in its early stage otherwise it may cause death.…”
Section: Introductionmentioning
confidence: 99%